The digital turn in architecture 1992-2010 - Carpo, Mario (London : Wiley, 2013)
The digital turn in architecture has gone through several stages and phases, and Architectural Design ( AD ) has captured them all. This anthology of AD 's most salient articles is chronologically and thematically arranged to provide a complete historical timeline of the rise to pre-eminence of computer-based design and production. A much-needed pedagogical and research tool, this synopsis also relates the present state of digitality in architecture to the history and theory of its recent development and trends. Architectural students, scholars, and practicing architects will find this book an invaluable reference.
Keywords: Architectural design -- Data processing; Architecture -- Data processing